Comparing bevacizumab and ranibizumab for initial reduction of central macular thickness in patients with retinal vein occlusions - Singer MA (Dove Medical Press, 2013)
Michael A Singer,1 Steven R Cohen,2 Sylvia L Groth,3 Salman Porbandarwalla21Medical Center Ophthalmology Associates (MCOA), San Antonio, Texas, USA; 2Department of Ophthalmology, University of Texas Health Science Center at San Antonio, San Antonio, Texas, USA; 3University of Minnesota Medical School, Minneapolis, Minnesota, USAPurpose: To examine short-term effects of ranibizumab versus bevacizumab on reduction of optical coherence tomography (OCT) central macular thickness (CMT) in patients with macular edema secondary to retinal vein occlusions (RVOs).Methods: This is a retrospective analysis in which patients with RVOs were injected with either bevacizumab or ranibizumab. At 2 weeks, all patients were injected with a dexamethasone intravitreal implant (Ozurdex®). CMT on OCT and best-corrected visual acuity were obtained at baseline, at 2 weeks (just prior to the dexamethasone intravitreal implant), and 6 weeks.Results: Sixty-four patients received injections (32 bevacizumab; 32 ranibizumab). At 2 weeks, bevacizumab group had a mean (±standard error of mean [SEM]) CMT reduction of 26.2% ± 3.4% versus 47% ± 3.5% reduction with ranibizumab (P < 0.0001). At 6 weeks, there was a 31.6% ± 3.2% CMT reduction with bevacizumab versus 52% ± 3.2% with ranibizumab (P < 0.0001). At 2 weeks, 15 (9%) of bevacizumab patients versus 25 (78.1%) ranibizumab patients achieved OCT CMT < 300 µm (P = 0.0192). At 6 weeks, 18 (56.3%) of bevacizumab compared to 30 (93.8%) of ranibizumab patients achieved CMT < 300 µm (P = 0.0010). Visual acuity was not significantly different at each time interval between the groups.Conclusion: Ranibizumab appears to have a greater effect in the short-term of decreasing macular edema on OCT when compared to bevacizumab in patients with RVOs.Keywords: anti-VEGF, central macular thickness, dexamethasone, intravitreal implant, macular edema, retinal vein occlusion